Influence of thickness on the drying kinetics of beet slices (Research, Society and Development, 2020)
The present work aims to evaluate the influence of thickness on the drying kinetics of beet slices and to adjust mathematical models (empirical and diffusive) to experimental data. The beets were cut in three different thicknesses (4, 6 and 8 mm) and the drying kinetics were carried out in an air circulation oven with a speed of 1.5 ms-1, at a temperature of 60 ºC. The empirical (Lewis, Page and Handerson and Pabis) and diffusive mathematical models considering the infinite wall geometry and the boundary condition of the third type were adjusted to the experimental data. The Page model presented as the best fit when compared to the others because it had higher values for R2 (R2> 0.99) and lower values for the chi-square function. The analytical solution of the diffusion equation with infinite wall geometry, showed an increase in the diffusivity and convective coefficient of heat transfer with an increase in the thickness of the slices and the low values of the number of biot indicate that the boundary condition used (third type) described the process satisfactorily. However, when there was an increase in the thickness of the slices, the lesser the variations in humidity inside them over time.